Transformasi Mutu Pendidikan melalui Kepemimpinan Sekolah yang Visioner - Rahayu, Siti Rahayu; Dedi Iswanto; Afitrianingsi; Nadia Khoirunisa; Mutiara Alfi; Nadia Zeniarti; Nurbaiti Oktasari (Universitas Muhammadiyah Kotabumi, 2025)
The quality of education in Indonesia continues to face numerous challenges, particularly at the school level, where disparities in resources and management affect learning outcomes. In this context, the visionary leadership of school principals emerges as a critical factor in driving sustainable improvements and transformative change. This study aims to explore how visionary leadership enhances educational quality and to identify the key characteristics and strategies principals use to effectively lead change. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews and participatory observations conducted at SMKS 17 Sukoharjo. The findings reveal that visionary principals transcend traditional administrative roles, positioning themselves as inspirational instructional leaders who actively foster collaboration among staff, promote pedagogical innovation, and enhance teacher professionalism. They also cultivate inclusive and meaningful learning environments that empower students as active participants in their education. Such leadership effectively bridges national education goals with the unique needs of the school community, fostering a shared awareness of quality education as a moral and social responsibility. Visionary principals demonstrate the ability to anticipate future challenges, adapt to evolving circumstances, and guide their schools toward long-term success. Therefore, strengthening visionary leadership through targeted development programs is essential, preparing principals to lead with clarity, purpose, and a continuous commitment to improvement in an ever-changing educational landscape.